La comunicación e interacción en la mediación pedagógica de los entornos virtuales de aprendizaje (Repertorio Científico, 2024)
Mediation, especially in distance education, is generated by reconstructing the knowledge scheme from teacher-student interaction and communication, facilitating closeness, trust and building the autonomy of the student. It implies knowledge through language and the ability to use it, in addition, it is strengthened through social experience, motivations and according to needs. The objective of this research was to determine the importance of communication as an element of pedagogical mediation for continuous improvement. This research was developed under a quantitative approach with a non-experimental, descriptive cross-sectional design. A questionnaire with 17 questions was applied, using the virtual tool Google Forms®, with the Likert measurement scale, where the degree of agreement or disagreement about the importance of communication was measured. There was a study population of 57 people, it was applied in two courses of the Sustainable Production Department, one group being High School students and another being Bachelor's students. As important results, they mention that the resources are available at all times and that they are accessed simply and quickly. The importance of empathy and motivation was reflected, which must occur in virtual environments in an intentional and assertive manner. Communication is relevant to students because it reconstructs schemes based on interaction in its different dimensions, generating closeness, motivation, autonomy, strengthening interpersonal relationships and favoring collaborative learning, among others.
Keywords: interaction, online learning, distance education, teaching and learning